Anthropogenic fires in Indonesia: a view from Sumatra - Bowen, M.R.; Bompard, J.M.; Anderson, I.P.; Guizol, P.; Gouyon, A. (Nova Science Publishers, 2001)
It is safe to regard all vegetation fires that occur on the main forested islands of Kalimantan, Sumatra and Irian Jaya as deliberately started by man. Accidental ignition caused by lightning strikes are rare under Indonesian conditions, exposed burning coal seems cost minor, highly localised damage and - as elsewhere through the world - discarded cigarettes are of no importance. Arson is often mentioned but no evidence offered, and even where land dispute tensions are high, arson is towards the bottom of the list of causes of vegetation fires. The roles played by the three major government agencies responsible for land management are discussed and it is concluded that their overlapping functions, together with the diffusion of responsibility, contribute greatly to the fire problem. It is concluded that the solution to Indonesia's fire problem lies largerly in much improved local level land-use planning and in strengthened local management that, together, foster local initiative and allow local autonomy. A continuation of the top-down, bureaucratic approach to fire management that focuses on fire suppression will fail in the field during the next el Nino drought as it did in 19997.